Comparative Language Of English And Mongondow (A Phonological Analysis) - Posuma, Fitri; Posumah, Jeni; Muntuuntu, Meity (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
This study conducted a phonological analysis comparing the vowel and consonant systems of English and Mongondow, a regional language spoken in North Sulawesi, Indonesia. The study aimed to identify similarities and differences in the phonological structure of the two languages, focusing on vowel and consonant phonemes. Data were collected through semi-structured interviews and observations with five native Mongondow speakers who are also English language learners. The results show that Mongondow has five vowel phonemes (A, I, U, E, O) and 17 consonant phonemes, while English has 12 pure vowels (including 8 diphthongs) and 24 consonants. These two languages have similarities in the classification of consonants based on place and manner of articulation, as well as voicing. However, Mongondow has a simpler vowel system and fewer consonant phonemes compared to English. In addition, Mongondow has unique consonant sounds, such as the alveolar trill /r/, which is rarely found in English. This study highlights the challenges faced by Mongondow speakers in pronouncing certain English sounds due to the influence of their mother tongue. The results of this study contribute to a better understanding of the phonological systems of both languages and provide insights for language learners and educators in addressing pronunciation difficulties. This research underscores the importance of phonological awareness in language learning and teaching, especially in multilingual contexts. The study concludes that understanding the phonological differences between English and Mongondow can help learners overcome pronunciation challenges and improve their language proficiency.